On the transitivisation of intransitive verbs. A Spanish-English contrastive corpus-based analysis of the verbs dormir and sleep - Rodríguez Arrizabalaga, Beatriz (Complutense Journal of English Studies, 2022)
This paper offers a Spanish-English contrastive corpus-based study of the possible transitive uses of the verbs dormir and sleep in Peninsular Spanish and the American and British varieties of English, respectively. The results obtained will show that their transitivity cannot be reduced, as usually pointed out in the bibliography, to the cognate object construction (sleep the sleep of the just/dormir el sueño de los justos), since, in addition to this pattern, both intransitive verbs undergo a transitivization process in other structures which have gone almost unnoticed in the literature: namely, (i) lexical causative constructions (dormir al niño/sleep the baby); (ii) transitive patterns with other non-subcategorised objects, different from cognates (dormir la borrachera/sleep the meal); (iii) constructions with direct objects promoted from adverbial prepositional phrases (dormir la mañana/sleep the morning); (iv) and finally, the way construction (sleep your way to the top), only attested in English. Our main objective will be to highlight the syntactico-semantic similarities and differences which these constructions exhibit in Spanish and English, as well as those concerning their frequency of occurence.